Unexpected pulmonary tumor: metastasis from a benign uterine leiomyoma in a post-menopausal woman: a case report - Efared, Boubacar; Atsame-Ebang, Gabrielle; Sani, Rabiou; Tahiri, Layla; Sidibe, Ibrahim Sory; Erregad, Fatimazahra; Hammas, Nawal; Smahi, Mohamed; Serraj, Mounia; Chbani, Laila; Fatemi, Hinde El (BMC research notes, 2017)
The occurrence of lung metastasis from benign uterine leiomyomas is rarely reported especially in post menopausal women. The pathogenesis of these metastatic benign tumors still remains a subject of various speculations. A 57-year-old woman presented with a chronic cough and dyspnea. She had undergone 8 years previously, hysterectomy for benign leiomyomas. A chest computed tomography scan showed a 4 cm solitary nodular parenchymal tumor that increased in size after 12 months. The histological analysis of the biopsy from this nodule showed a benign tumor with regular spindle cells disposed in intersected fascicles. At immunohistochemical analysis, the tumor cells were positive for smooth muscle markers and oestrogen-progesterone receptors with a low mitotic index assessed by Ki-67. These features were consistent with a benign metastasizing uterine leiomyoma. At the multidisciplinary meeting, prescription of an aromatase inhibitor has been decided for the patient. Benign metastasizing uterine leiomyomas of the lung are very rare tumors. Although extremely rare in post menopausal women, their diagnosis should be considered in symptomatic patients with a history of hysterectomy for leiomyomas.